Teaching sentence fluency using Dizzy - Culham, Ruth.; Winter, Jonah (New York : Scholastic, 2008)
Presents reproducible forms, including checklists, graphic organizers, rubrics, and scoring sheets designed to improve writing skills in second-grade students.
"Grade 2" Cover.
Professional.
Professional
Keywords: Creative activities and seat work; English language -- Composition and exercises -- Study and teaching (Elementary); Teaching -- Aids and devices; Creative activities; English language -- Composition and exercises -- Study and teaching; Teaching -- Aids and devices